(untitled) (Eurasian Journal of Philology Science and Education, 2016)
The article deals with the substantial components of the concept of «Oriental City». Universal, national-cultural and individual layers are identified. It holds in-detail description of the «layer» of the concept of «Oriental City». As the material of description the works of the famous contemporary writers T. Zulfikarov and Y. Ilyasov were considered. The researcher highlights language means that represent the concept of «Oriental City». The focusing on the context of language units representing the concept of «Oriental City» gives an opportunity to reveal the periphery of the concept, to describe the meaning shades that are not fixed in any lexicographical sources, and finally to discover the peculiarities of the studied concept in linguocultural aspect. The technique of the conceptual analysis presented in the article can be used at research of language of any work of art.